Proceedings of the 27th Annual ACM Symposium on User Interface Software and Technology 2014
DOI: 10.1145/2642918.2647403
|View full text |Cite
|
Sign up to set email alerts
|

Tohme

Abstract: Building on recent prior work that combines Google Street View (GSV) and crowdsourcing to remotely collect information on physical world accessibility, we present the first "smart" system, Tohme, that combines machine learning, computer vision (CV), and custom crowd interfaces to find curb ramps remotely in GSV scenes. Tohme consists of two workflows, a human labeling pipeline and a CV pipeline with human verification, which are scheduled dynamically based on predicted performance. Using 1,086 GSV scenes (stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, on‐site assessments should be conducted when characterizing micro‐environments for special activities, such as cycling (Vanwolleghem et al ). Several studies applied computer vision to Street View imagery, for example, to identify sidewalk curbs (Hara et al ), or to determine the geographic location of photographs based on reference imagery extracted from Street View (Zamir and Shah ). Yin et al () provide technical details on downloading and assembling Street View images and their use for pedestrian detection using machine vision and learning technology.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on‐site assessments should be conducted when characterizing micro‐environments for special activities, such as cycling (Vanwolleghem et al ). Several studies applied computer vision to Street View imagery, for example, to identify sidewalk curbs (Hara et al ), or to determine the geographic location of photographs based on reference imagery extracted from Street View (Zamir and Shah ). Yin et al () provide technical details on downloading and assembling Street View images and their use for pedestrian detection using machine vision and learning technology.…”
Section: Related Workmentioning
confidence: 99%
“…Geolocated street‐level photographs are an important data source for a variety of transportation analysis tasks, including the identification of road features, such as traffic signs (Gonzalez et al ), the evaluation of wheelchair accessibility of sidewalks (Hara et al ), or the deployment of navigational tools for visually impaired citizens (Guy and Truong ). Mapillary is the first platform to provide detailed street photos based on crowdsourcing, adding to the list of Web 2.0 applications that administer and facilitate the collection of Volunteered Geographic Information (VGI) (Goodchild ).…”
Section: Introductionmentioning
confidence: 99%
“…In an early feasibility study [9] manually created a database consisting of 100 images from Google Street View. Researches from the same group afterwards studied the combination of crowdsourcing and Google Street View to identify street-level accessibility problems [10] and developed an online curb ramp data collection system Tohme [11]. The system enables workers to remotely label curb ramps through Google Street View with the assistance of computer vision and machine learning techniques.…”
Section: Crowdsourcing Using Street-level Imagerymentioning
confidence: 99%
“…Recent studies [8][9][10][11]31] have shown that the combination of street-level imagery with micro-task crowdsourcing can successfully engage a larger number of contributors -possibly unfamiliar with the targeted urban area -through object annotation tasks. While demonstrating the feasibility of a micro-task crowdsourcing approach, these works do not fully address the important quality and scalability issues that generally characterize large scale object annotation campaigns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation